INTERNALISASI NILAI ASWAJA DALAM PENDIDIKAN BERPERADABAN DI ERA 4.0 - Jamal Ghofir (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2019)
Nahdlatul Ulama with its active role participated in the intellectual life of the nation, from the colonial era to the present, which is always consistent in the line of struggle. Nahdlatul Ulama as a religious social organization which is considered old-fashioned and narrow-minded is not an obstacle in serving and basing its life for the sake of religion and nation. History will be able to prove how Nahdlatul Ulama's intellectual role is without having to brag about modernity.